Diagnostic accuracy of HbA1c in diabetes between Eastern and Western. (2nd May 2013) - Yan, Shuang; Liu, Siying; Zhao, Yashuang; Zhang, Wencui; Sun, Xiaohui; Li, Jianing; Jiang, Fuli; Ju, Jiaming; Lang, Ning; Zhang, Yingqi; Zhou, Weiyu; Li, Qiang
Abstract Background In 2010, the American Diabetes Association recommended the use of HbA1c as a diagnostic criterion for diabetes. However, HbA1c is not an accepted diagnostic tool for diabetes in Eastern Asia, because genetic differences compromise the standardization of the diagnostic cut‐off point. Objectives This study evaluated differences in the use of HbA1c for diagnosing diabetes in Eastern and Western populations and investigated whether HbA1c cut‐off point of ≥ 6·5% is diagnostic of diabetes in patients from Eastern Asia. Methods Literature was obtained from MEDLINE, EMBASE and Cochrane databases. The pooled sensitivity and specificity of each HbA1c cut‐off point were extracted and compared between Western and Eastern populations. Differences in the cut‐off point for diagnosing diabetes in each region were compared by examining differences in the area under summary receiver operating characteristic (SROC) curves. Results Twelve publications from Eastern countries (n = 59 735) and 13 from Western countries (n = 22 954) were included in the analysis. Areas under SROC curves in the Eastern and Western groups were 0·9331 and 0·9120, respectively (P = 0·98). The cut‐off point of the highest Youden index was 6·0%. At the HbA1c cut‐off point of 6·5%, the pooled sensitivity and specificity were 58·7% and 98·4% for Eastern countries and 65·5% and 98·1% for Western countries, respectively. Conclusions HbA1c exhibits the same diagnostic value for diabetes in Eastern and Western populations. In both populations, HbA1c levels > 6·0% identify the population at high risk of diabetes, and HbA1c > 6·5% is diagnostic of clinically established diabetes.